The equity risk premium: A review of models - Fernando Duarte; Carlo Rosa (Federal Reserve Bank of New York, 2015)
We estimate the equity risk premium (ERP) by combining information from twenty models. The ERP in 2012 and 2013 reached heightened levels - of around 12 percent - not seen since the 1970s. We conclude that the high ERP was caused by unusually low Treasury yields.
Keywords: C58; G00; G12; G17; 330; equity premium; stock returns